Extrachromosomal replication of shuttle vectors in Dictyostelium discoideum. - Firtel, R A (1985)
We cloned a 12.3-kilobase (kb) endogenous plasmid, Ddp1, found in several wild-type and laboratory strains of Dictyostelium discoideum into pBR322. The cloned plasmids have been used to cotransform D. discoideum cells with B10S, a transformation vector carrying a gene fusion conferring resistance to G418. Whereas B10S DNA alone appears to integrate in a tandem array, the cloned Ddp1 plasmids replicate extrachromosomally and are stably maintained in the absence of selection with an average copy number of 50 to 100 copies per cell. The Ddp1-derived plasmids can be directly recovered by transforming Escherichia coli with bulk nuclear DNA from these cells. Preliminary deletion analysis indicates that not all regions of Ddp1 are necessary for stable replication in D. discoideum. Several recombinant vectors which replicate extrachromosomally in D. discoideum were also isolated. One contains the Act6-neor gene fusion from B10S recombined into one of the cloned derivatives of Ddp1 and can be used to directly transform D. discoideum amoebae, selecting for G418 resistance. Another recombinant is only 5.6 kb and resulted from a deletion of a 16.6-kb cloned Ddp1 hybrid plasmid. An analysis of the vector DNAs present in clones derived from single D. discoideum transformants is also described.